2014
DOI: 10.1063/1.4905137
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-Seebeck effect in spin-valve with in-plane thermal gradient

Abstract: Effects of grain cluster size on coercivity and giant magnetoresistance of NiFe/Cu/CoFe/Cu/NiFe pseudo spin valves Appl.We present measurements of magneto-Seebeck effect on a spin valve with in-plane thermal gradient. We measured open circuit voltage and short circuit current by applying a temperature gradient across a spin valve stack, where one of the ferromagnetic layers is pinned. We found a clear hysteresis in these two quantities as a function of magnetic field. From these measurements, the magneto-Seebe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Resistance of the sample depends on the mutual orientation of magnetization between free and fixed layer ( Fig. 1d) which originates from current in-plane GMR effect 21 . Clear GMR hysteresis is observed ( Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance of the sample depends on the mutual orientation of magnetization between free and fixed layer ( Fig. 1d) which originates from current in-plane GMR effect 21 . Clear GMR hysteresis is observed ( Fig.…”
mentioning
confidence: 99%
“…These torques can be attributed to either Slonczewski's spin-transfer torque (STT) 13 or field-like torque (FLT) 3,8,14 . STT arises when ferromagnet absorbs spin current generated by many ways like spin-Hall effect (SHE) 15,16 , spin-pumping 17 , spin-Nernst effect 18 , spin-(dependent) Seebeck effect [19][20][21] etc. Field-like torque is generally observed in asymmetric magnetic tunnel junctions (MTJ) with current perpendicular to the plane (CPP) geometry 3,14,22 and ferromagnet/heavy metal bilayer where Rashba 8 or Dressulhous 7 spin orbit interaction is present.…”
mentioning
confidence: 99%
“…Gravier [12] and Sakurai [13] et al reported a fielddependent thermopower in Fe/Cr and Co/Cu multilayers and they discussed little on physics hidden behind it. Very recently, Jain [14] et al reported a tiny field-dependent Seebeck effect in CoFe/Cu/CoFe/IrMn/Ru spin valves. They further attributed its field dependence to the trivial origin that different resistances in parallel (P) state and antiparallel (AP) state resulted in different Seebeck coefficients accordingly.…”
mentioning
confidence: 99%
“…Nernst effect gives these materials an advantage for application and increases the usability of these materials in spin-based devices [12,64]. Tremendous research efforts have been devoted in spin caloritronics to investigate the interplay of spin and thermoelectric transport phenomena [1,6,7,8,9]. La 0.7 Sr 0.3 MnO 3 (LSMO) is an important material for spintronics due to its large spin-polarization [3].…”
Section: Introductionmentioning
confidence: 99%